2014
DOI: 10.3390/ijms151119369
|View full text |Cite
|
Sign up to set email alerts
|

Improved Release and Metabolism of Flavonoids by Steered Fermentation Processes: A Review

Abstract: This paper provides an overview on steered fermentation processes to release phenolic compounds from plant-based matrices, as well as on their potential application to convert phenolic compounds into unique metabolites. The ability of fermentation to improve the yield and to change the profile of phenolic compounds is mainly due to the release of bound phenolic compounds, as a consequence of the degradation of the cell wall structure by microbial enzymes produced during fermentation. Moreover, the microbial me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
120
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(145 citation statements)
references
References 88 publications
4
120
0
2
Order By: Relevance
“…Especially, the higher antioxidant activity of fermented buckwheat Makgeolli than that of buckwheat Makgeolli might result from R. oligosporus that can produce α‐amylase and endogenous carbohydrate‐cleaving enzymes, since these enzymes can produce polyphenols from carbohydrates‐conjugated phenolic compounds during fermentation of buckwheat (McCue & Shetty, 2003). In addition, R. oligosporus is known to produce β‐glucosidase, β‐glucuronidase, or xylanase to degrade cell wall matrix (Huynh, Van Camp, Smagghe, & Raes, 2014). Thus, during fermentation, R. oligosporus might bio‐convert bound‐phenolic compounds into unbound phenolics as aglycone forms (Huynh et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially, the higher antioxidant activity of fermented buckwheat Makgeolli than that of buckwheat Makgeolli might result from R. oligosporus that can produce α‐amylase and endogenous carbohydrate‐cleaving enzymes, since these enzymes can produce polyphenols from carbohydrates‐conjugated phenolic compounds during fermentation of buckwheat (McCue & Shetty, 2003). In addition, R. oligosporus is known to produce β‐glucosidase, β‐glucuronidase, or xylanase to degrade cell wall matrix (Huynh, Van Camp, Smagghe, & Raes, 2014). Thus, during fermentation, R. oligosporus might bio‐convert bound‐phenolic compounds into unbound phenolics as aglycone forms (Huynh et al., 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, R. oligosporus is known to produce β‐glucosidase, β‐glucuronidase, or xylanase to degrade cell wall matrix (Huynh, Van Camp, Smagghe, & Raes, 2014). Thus, during fermentation, R. oligosporus might bio‐convert bound‐phenolic compounds into unbound phenolics as aglycone forms (Huynh et al., 2014). Furthermore, during the process of brewing Makgeooli, different kinds of fungi ( Aspergillus , Rhizopus ), yeast, and various lactic acid bacteria (Nile, 2015) can produce tannase, phenolic acid decarboxylase, benzyl alcohol dehydrogenase, and β‐glucosidase that can degrade some phenolic compounds (Landete et al., 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…이것은 발효과정 중에 총 페놀 화합물이 증가하 기 때문으로 사료되며 렌즈콩에서 유래하는 고혈압 예방의 기능 성성분으로 유망하다고 하겠다 (13). 발효기술은 콩류의 발효과정 에서 독특한 대사물질의 전환으로 더 높은 품질과 증가된 활성 을 유도할 수 있다 (14). 본 총설은 렌즈콩의 영양성분과 생리활 성을 요약하고 추후 발효기술을 이용한 응용범위를 확대하여 식 품산업에 응용하기 위한 자료를 제공하고자 한다.…”
Section: 한국식품과학회지 제 47 권 제 3 호 (2015)unclassified
“…Consequently, the free phenolic compounds as well as bound forms are more available for their extraction. Among these enzymes, b-glucosidase has been widely reported as an enzyme responsible for catalyzing the hydrolysis of b 1-4 bounds in alkyl and aryl-b-D-glucosides to release phenolic aglycone fractions (Huynh et al, 2014). Cheng et al (2013) reported that R. oligosporus has potential to significantly enhanced the content of total phenolic and antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%